2016
DOI: 10.1016/j.jpeds.2016.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Risk for Sudden Unexpected Infant Death in Children of Adolescent Mothers: A Qualitative Study

Abstract: Among focus group participants, adherence with safe sleep practices was poor despite awareness of the American Academy of Pediatrics recommendations. Many mothers expressed beliefs and instincts that infants were safe in various unsafe sleep environments. Future study should investigate the efficacy of alternative educational strategies, including education of grandmothers, who have significant influence over adolescent mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 18 publications
4
33
1
Order By: Relevance
“…There is widespread use of bumper images in the media and displays in stores (Joyner et al 2009; Kreth et al 2017) implying that bumpers are safe. Along with other studies (Colvin et al 2014; Caraballo et al 2016), we found that many mothers are unaware of the dangers of crib bumpers, with 59% of crib bumper mothers in our study choosing crib bumpers because “they are safe. ” Advising parents to avoid soft bedding, including crib bumpers, to prevent SIDS may be a confusing and mixed message for many parents.…”
Section: Discussionsupporting
confidence: 84%
“…There is widespread use of bumper images in the media and displays in stores (Joyner et al 2009; Kreth et al 2017) implying that bumpers are safe. Along with other studies (Colvin et al 2014; Caraballo et al 2016), we found that many mothers are unaware of the dangers of crib bumpers, with 59% of crib bumper mothers in our study choosing crib bumpers because “they are safe. ” Advising parents to avoid soft bedding, including crib bumpers, to prevent SIDS may be a confusing and mixed message for many parents.…”
Section: Discussionsupporting
confidence: 84%
“…Despite evidence that breastfeeding has advantages for mother and child health (Stuebe 2009 ), breastfeeding rates remain low in the US among young, low-income and African-American women (McDowell et al 2008 ). Additionally, although the American Academy of Pediatrics (Task Force on Sudden Infant Death Syndrome 2016 ) recommends that infants be placed in supine sleep positions in their own beds in order to reduce the risk of sleep-related infant deaths, infants born to young, low-income mothers have a relatively high risk for prone placement and for co-sleeping (Colson et al 2009 ; Caraballo et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“… 18 In a study with adolescent mothers in the USA, the authors report how maternal instincts and information from mothers’ mothers overruled the safety advice given to them by health professionals. 19 Similarly, the mothers in our study made it clear that they needed credible sources of advice that worked with their own instincts, rather than against them. Our interpretation is that mothers do not perceive themselves as prioritising infant comfort over safety, as was suggested in the study with teen mothers, 19 but rather that they prioritise infant comfort over a small perceived risk of a very rare event.…”
Section: Discussionmentioning
confidence: 71%
“… 19 Similarly, the mothers in our study made it clear that they needed credible sources of advice that worked with their own instincts, rather than against them. Our interpretation is that mothers do not perceive themselves as prioritising infant comfort over safety, as was suggested in the study with teen mothers, 19 but rather that they prioritise infant comfort over a small perceived risk of a very rare event. Another US study 20 reported that the mothers talked about a maternal awareness of the baby during sleep, similar to the ‘mum sleep’ described in the current study.…”
Section: Discussionmentioning
confidence: 71%